(untitled) (Biological Sciences - PJSIR, 2019)
This study was carried out to assess the quality attributes of rice varieties named as Super Kernel, Super Basmati, Basmati-515, PK-386, Kainat and IRRI-9 after milling for the establishment of claimed standards for approved varieties to prohibit rice adulteration. Furthermore, brown and white fractions of selected varieties were evaluated for physical characteristics including grain size (grain length/grain width ratio) thousand kernel weight (TKW) and bulk density. Mean values for grain size (L/W ratio), bulk density and TKW were ranged from 3.86±0.30 to 4.59±0.32, 0.71±0.08 to 0.80±0.10g/mL and 16.74±1.18 to 17.96±0.85g among the rice cultivars. Overall, grain size (4.00±0.21 to 4.48±0.35 and 4.14±0.43 to 4.81±0.37), bulk density (0.66±0.05 to 0.72±0.09g/mL and 0.77±0.05 to 0.82±0.27g/mL) and TKW (18.00±0.48 to 19.22±0.35g and 15.91±0.84 to 16.78±0.32g) varied significantly in brown and white rice samples. The lowest decrease in length after milling was seen in white rice of Kainat (8.90%) followed by PK-386 (9.86%) and Basmati-515 (10.70%), while the IRRI-9 showed highest decrease (11.84%) as compare to brown rice. Likewise, lowest increase in width was observed in IRRI-9 (10.27%) as compared to Kainat (19.87%) which indicates that IRRI-9 had more width. Conclusively, grain dimensions, kernel weight and bulk density of both brown and white rice fractions were significantly influenced by genetic, environmental and socio-economic factors among locations and cultivars. There is an urgent need to discriminate among premium and local rice varieties of country to boost up the export and foreign earnings.